Live at school: relationships between school and families in two rural secondary education institutions (Córdoba, Argentina) - Verónica Virginia Ligorria; María Florencia Serra (Educazione Interculturale)
The present work proposes the dynamics that the school-family relationship takes in rural secondary education with shelter, in two schools located in the western zone of the province of Cordoba (Argentina). The relationships between school and family are explored, investigating the links linked to living at school and the challenges and conflicts that such dynamics can generate in students’ families. For this study, the conclusions of two own doctoral investigations are taken up in which interviews, observations and document analysis were carried out (Ligorria, 2020; Serra, 2022). Entering and remaining in these schools means a commitment to ensuring secondary education and implies that young people go through uprooting, and families do without them as assistant, choose to live together in the shelter, overcoming fears derived from it (especially when it comes to mixed shelters), and that they are in charge of adults (shelter preceptors) who regulate coexistence, generating training strategies typical of the daily bond that goes beyond what exclusively pedagogical.